Satellite Attitude Control System Simulator - G.T. Conti; L.C.G. Souza (Shock and Vibration)
Future space missions will involve satellites with great autonomy and stringent pointing precision, requiring of the Attitude Control Systems (ACS) with better performance than before, which is function of the control algorithms implemented on board computers. The difficulties for developing experimental ACS test is to obtain zero gravity and torque free conditions similar to the SCA operate in space. However, prototypes for control algorithms experimental verification are fundamental for space mission success. This paper presents the parameters estimation such as inertia matrix and position of mass centre of a Satellite Attitude Control System Simulator (SACSS), using algorithms based on least square regression and least square recursive methods. Simulations have shown that both methods have estimated the system parameters with small error. However, the least square recursive methods have performance more adequate for the SACSS objectives. The SACSS platform model will be used to do experimental verification of fundamental aspects of the satellite attitude dynamics and design of different attitude control algorithm.